Parenting Challenges and Opportunities among Families Living in Poverty - Lana O. Beasley; Jens E. Jespersen; Amanda S. Morris; Aisha Farra; Jennifer Hays-Grudo (Social Sciences, 2022)
Poverty-related stressors have been found to impact parenting behaviors which can result in adverse outcomes for children. The current qualitative study focused on understanding the challenges of caregivers (N = 70) living in poverty. The sample was diverse and included mothers, fathers, and grandparents raising grandchildren. Stories of caregivers were gathered to improve the understanding of families living in poverty in an effort to work towards changing how our world supports families that are vulnerable. Results indicate that families experiencing poverty and related risk factors experience challenges in the realm of child safety, education, and racism/prejudice. Families also discussed ways to improve their environment which included increased financial resources, increased access to high-quality healthcare and childcare, and positive environmental change. Note that the current study outlines the complexity of parenting in poverty and that associated challenges are intertwined. Recommendations are made to address systemic barriers at the individual and community level in an effort to better support caregivers experiencing adversity and parenting in the 21st century.